Traumatic Atlanto-occipital Dislocation in Children Followed by Hydrocephalus – A Case Report and Literature Review - Formentin, Cleiton; Santos, Lucas de Souza Rodrigues dos; Maeda, Fernando Luis; Tedeschi, Helder; Ghizoni, Enrico; Joaquim, Andrei F. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Traumatic atlanto-occipital dislocation (TAOD) are uncommon injuries associated with high immediate mortality rate and occurs more than twice in children than adults, due to biomechanical properties and immaturity of children's cervical spine. We report a pediatric patient with TAOD, who underwent occipitocervical stabilization and also developed a late hydrocephalus requiring a shunt procedure. A six-year-old boy was admitted to the emergency department after a car accident with refractory cervical pain. A cervical computed tomography (CT) scan showed an anterior C1–C2 level hematoma, and a dynamic CT scan demonstrated an increasing basion-dens interval on extension. Cervical magnetic resonance imaging (MRI) showed discontinuity of the tectorial membrane and diffused hyperintense signal on the left alar ligament. These findings were attributed to TAOD, and an occipitocervical fusion was performed. The pain and neurological status improved after surgery, but after 3 months he returned with persistent vomiting, headache, and a CT scan showing hydrocephalus. Then, a ventriculoperitoneal shunt was performed, improving the symptoms. One year after the injury, the patient remained asymptomatic, and a later radiography demonstrated satisfactory bone fusion. In conclusion, the decision-making process regarding treatment should consider several clinical and radiographic findings. Occipitocervical fusion is the treatment of choice, while hydrocephalus is not an unusual complication in children.
Keywords: atlanto-occipital dislocation; pediatric spine; trauma; hydrocephalus